Konsep Tabayyun Sebagai Prinsip Dasar Manajemen Pendidikan Islam - Taufiq, Muhammad; Hasnida, Hasnida (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to examine the concept of tabayyun from the perspective of Ulumul Qur'an and analyse its implications for Islamic education management. The method used is a literature study with a qualitative-descriptive approach. Data was collected through analysis of Qur'anic verses related to the principle of tabayyun, tafsir studies, and relevant Islamic education management literature. The analysis was conducted by interpreting the conceptual meaning of tabayyun and relating it to the practice of managing Islamic educational institutions. The results of the study indicate that tabayyun has a strategic position as a managerial principle that emphasises information verification, caution in decision-making, and fairness in problem solving. The application of tabayyun not only functions in the realm of individual ethics, but can also be integrated as the basis for information management, quality assurance, and governance of Islamic educational institutions. Thus, the integration of the principle of tabayyun has the potential to strengthen Islamic education management that is professional, accountable, and in line with Qur'anic values